(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2019)
The present essay deals with the progressive introduction of Plea Bargaining in our legal system, discussing advantages and disadvantages of the doctrine, considering the major purposes of the jurisdiction, among which certainly is not to lead innocent people to confess a crime that they did not commit.